Answer:
Part 1 - ε = (2π²r²B/T)cosωt
Part 2: ε = B√[(2πr{(πr/T)² + x²}]Sin(ωt + Ф) where Ф = tan⁻¹(πr/xT)
Step-by-step explanation:
Part 1. Since the magnetic field is sinusoidal and has a period of T and amplitude of B, it is of the form B' = Bsinωt where ω = 2π/T
Now, the induced emf in the circular loop is ε = dΦ/dt where Φ = magnetic flux through circular loop of wire. Φ = AB' where A = area of loop of wire, A = πr² where r = radius of loop of wire.
So, ε = dΦ/dt
ε = dAB'/dt
= AdB'/dt
= AdBsinωt/dt
= ωABcosωt
= (2πAB/T)cosωt
with A = πr²,
ε = (2π²r²B/T)cosωt
Part 2
If the radius of the loop is increasing at a constant rate x, then the induced emf is
ε = dΦ/dt
= dAB'/dt
= AdB'/dt + B'dA/dt
= πr²dBsinωt/dt + (Bsinωt)dπr²/dt
= (ωπr²)Bcosωt + (Bsinωt)2πrdr/dt
= (ωπr²)Bcosωt + (Bsinωt)2πrx
= (2π²r²B/T)cosωt + (2πrxB)sinωt
Writing this in compound angle form,
ASin(ωt + Ф) = AsinФcosωt + AcosФsinωt
comparing both expressions,
AsinФ = 2π²r²B/T and AcosФ = 2πrxB
(AsinФ)² + (AcosФ)² = A²
(2π²r²B/T)² + (2πrxB)² = A²
B²[(2πr{(πr/T)² + x²}] = A²
B√[(2πr{(πr/T)² + x²}] = A
tanФ = AsinФ/AcosФ
tanФ = 2π²r²B/T ÷ 2πrxB
tanФ = πr/xT
Ф = tan⁻¹(πr/xT)
ε = B√[(2πr{(πr/T)² + x²}]Sin(ωt + Ф) where Ф = tan⁻¹(πr/xT)